Electrically Evoked Compound Action Potentials Recorded From the Sheep Spinal Cord. Issue 4 (11th July 2013) - Parker, John L.; Karantonis, Dean M.; Single, Peter S.; Obradovic, Milan; Laird, James; Gorman, Robert B.; Ladd, Leigh A; Cousins, Michael J.
<x xml:space="preserve">Abstract</x> Objectives The study aims to characterize the electrical response of dorsal column axons to depolarizing stimuli to help understand the mechanisms of spinal cord stimulation (SCS) for the relief of chronic pain. Materials and Methods We recorded electrically evoked compound action potentials (ECAPs) during SCS in 10 anesthetized sheep using stimulating and recording electrodes on the same epidural SCS leads. A novel stimulating and recording system allowed artifact contamination of the ECAP to be minimized. Results The ECAP in the sheep spinal cord demonstrates a triphasic morphology, with P1, N1, and P2 peaks. The amplitude of the ECAP varies along the length of the spinal cord, with minimum amplitudes recorded from electrodes positioned over each intervertebral disc, and maximum amplitudes recorded in the midvertebral positions. This anatomically correlated depression of ECAP also correlates with the areas of the spinal cord with the highest thresholds for stimulation; thus regions of weakest response invariably had least sensitivity to stimulation by as much as a factor of two. The choice of stimulating electrode location can therefore have a profound effect on the power consumption for an implanted stimulator for SCS. There may be optimal positions for stimulation in the sheep, and this observation may translate to humans. Almost no change in conduction velocity (∼100 ms) was observed with increasing currents from threshold to twice threshold, despite increased Aβ fiber recruitment. Conclusions Amplitude of sheep Aβ fiber potentials during SCS exhibit dependence on electrode location, highlighting potential optimization of Aβ recruitment and power consumption in SCS devices.